2020
DOI: 10.1097/md.0000000000021871
|View full text |Cite
|
Sign up to set email alerts
|

Blood neurofilament light chain in Parkinson disease and atypical parkinsonisms

Abstract: Background: Neurofilament light chain (NfL), an index of neuroaxonal injury, is a promising diagnostic and prognostic fluid biomarker with high translational value in many neurodegenerative disorders. Blood NfL measurement has been an exciting and active field of research in idiopathic Parkinson disease (PD) and atypical parkinsonisms. However, blood NfL levels in these parkinsonisms from existing literature were inconsistent. No comprehensive meta-analysis has ever been conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[7,8] These proteins are synthesized in the body of the neuron and assembled into intermediate filaments in the axon, where they provide stability. [9] Many studies indicate that high levels of pNfL in CSF have been found in different neuroinflammatory and neurodegenerative diseases, such as dementia, [10] Alzheimer's disease (AD), [11] Parkinsonian disorders, [12] and amyotrophic lateral sclerosis. [13] The level of pNfL is higher in AD patients than healthy populations and is also associated with disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] These proteins are synthesized in the body of the neuron and assembled into intermediate filaments in the axon, where they provide stability. [9] Many studies indicate that high levels of pNfL in CSF have been found in different neuroinflammatory and neurodegenerative diseases, such as dementia, [10] Alzheimer's disease (AD), [11] Parkinsonian disorders, [12] and amyotrophic lateral sclerosis. [13] The level of pNfL is higher in AD patients than healthy populations and is also associated with disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising biomarkers for assessing the risk of neurological deterioration is initial levels of serum neurofilament light chain (NfL), a member of the family of neurofilament proteins that maintains the structural integrity of neuronal cytoskeleton. NfL is released into cerebrospinal fluid and blood during CNS injury and, as such, is a highly reliable liquid biomarker for neuroaxonal injury and for monitoring the progression of various neurodegenerative conditions (e.g., Parkinson's disease, multisystem atrophy, Alzheimer disease) and neuroinflammatory disorders (e.g., multiple sclerosis) [60][61][62][63][64]. In WD, positive correlations have been observed between sNfL levels and the severity of neurological disease including neurological phenotype (compared to hepatic and asymptomatic) and neurological disease severity scale (UWDRS) [27].…”
Section: Risk Factors For Early Neurological Deterioration In Wdmentioning
confidence: 99%
“…Thus, the approach has been successful recently and offers great promises for the near future [ 17 , 18 ]. The EVs, released by neurons and astrocytes of patients affected by neurodegenerative disease, can be identified by specific biomarkers found in their cargoes, such as Aβ and phosphorylated tau in AD, α-synuclein in PD, and the transactive response DNA/RNA binding protein of 43kDa (TDP-43) in ALS [ 13 , 19 , 20 , 21 , 22 ] ( Table 1 ). Other biomarkers investigate the subclinical declines of the diseases, for example, the decline of middle age in AD.…”
Section: From Molecules To Extracellular Vesiclesmentioning
confidence: 99%
“…The choice of this disease has been made to illustrate its general properties. The task is to provide a current landscape, largely common to PD [ 21 , 29 , 36 ] but not always to other neurodegenerative diseases (see, for example, [ 9 , 17 , 28 , 31 , 32 ]).…”
Section: Ad and Its Multiple Fluid Biomarkersmentioning
confidence: 99%